THE ESSENCE OF PARALLEL IMPORT AND PROBLEMS OF ITS REGULATION IN THE REPUBLIC OF UZBEKISTAN (TSUL LEGAL REPORT, 2026)
This article discusses the definitions of various scholars given to the concept of parallel import, phenomenon’s ever-increasing actuality and economic significance, as well as the issues of its legal regulation by states. The importance of exhaustion regime of intellectual property rights, its reflection in international agreements and the role in WTO system and international trade at large are mentioned. The problems associated with legislation coverage of this concept in our national civil and customs law are discussed and the procedure for parallel imports and exhaustion in the Republic of Uzbekistan are reviewed in the case of courts. Furthermore, this paper articulates that economic analysis of parallel imports and their effects is of high importance when adopting Article 6 of TRIPS Agreement. The relationship between parallel imports and access to pharmaceuticals is analyzed and the author made a judgment on what factors should be considered by governments on complying national legislation with international norms that permit parallel trade of IP objects.